Evidence of securitisation in the economic sector of security in Europe? Russia's economic blackmail of Ukraine and the EU's conditional bailout of Cyprus. Issue 2 (3rd April 2019) - Floyd, Rita
ABSTRACT: Although the Copenhagen school's securitisation theory and their sectoral analysis are integral parts of European security studies, the school's economic sector of security has almost been completely ignored. In this article I examine why this is, and whether it makes sense to retain this sector. In the process I flesh out the logic of securitisation in the economic sector. I suggest that one reason why the economic sector of security has been neglected is that real life examples fitting the Copenhagen school's logic of security as the exception have – in this sector – remained outstanding. Research in other sectors of security has shown however that securitisation does not need to include extraordinary countermeasures; instead it can play out below the level of the exception. Using alternative formulations developed in securitisation studies that relax the threshold for the success of securitisation, I attempt to locate evidence of economic securitisation by looking at two empirical cases. 1) Russia's economic blackmail of Ukraine at the start of that country's ongoing crisis. 2) The EU's conditional bailout of Cyprus during the Eurozone crisis which necessitated capital controls. On the basis of the empirical evidence gathered I conclude by arguing the case for the economic sector of security.